All Days 2000
DOI: 10.2118/59438-ms
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Underground Gas Storage Simulator

Abstract: Japan National Oil Corporation (JNOC) is conducting a survey on underground gas storage (UGS) using inert gas as cushion gas, which makes good use of assets of depleted gas or gas condensate reservoirs. Since the Japanese regulation for a heating value of city gas is extremely strict, a heating value and hence composition of gas withdrawn from those reservoirs must be carefully predicted to properly design UGS projects. JNOC has developed an UGS simulator, which can rigorously evaluate a heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Kurihara modified the traditional component state equation and established a component state equation with the consideration of molecular diffusion and water-soluble gas adsorption, and developed a simulator. The simulator was targeted more than any other commercial software for examining the variation in the gas component and calculation of the pore volume, but it has not been widely used [16]. Tan established a mathematical model for underground gas storage, which was rebuilt by using exhausted gas reservoirs.…”
Section: Research On Gas Loss and Mathematical Model In Injection Andmentioning
confidence: 99%
“…Kurihara modified the traditional component state equation and established a component state equation with the consideration of molecular diffusion and water-soluble gas adsorption, and developed a simulator. The simulator was targeted more than any other commercial software for examining the variation in the gas component and calculation of the pore volume, but it has not been widely used [16]. Tan established a mathematical model for underground gas storage, which was rebuilt by using exhausted gas reservoirs.…”
Section: Research On Gas Loss and Mathematical Model In Injection Andmentioning
confidence: 99%
“…The influence of various factors on the solubility of water in gas phase [18] Zuluaga et al [21] also conducted some studies in porous environment and concluded that increasing Debbi increases the phenomenon of water evaporation and water salinity decreases it.…”
Section: Fig5mentioning
confidence: 99%
“…Since then, a lot of scientists have conducted rock physical modelling experiment and numerical simulation studies (Haln and Monger 1990;Wozinak et al 1997), these basically figure out: when the gas was injected rapidly into the storage, it would cause a series of reactions, such as the instigation of the Jamin effect, flow-around, water-locking, gas-locking, and emptying (Kurihara et al 2000). These factors exert significant effects on production efficiency in underground gas storage facilities (Udegbunan et al 1994).…”
Section: Introductionmentioning
confidence: 99%